PENGARUH CORPORATE GOVERNANCE DAN KOMPENSASI MANAJEMEN TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR PERTAMBANGAN DI INDONESIA - Jane Syafira Suwandani (2021)
This research aims to analyze the effect of corporate governance mechanisms and management compensation on tax avoidance on listed mining companies in Indonesia Stock Exchange in the period 2017-2019. Corporate governance mechanisms is proxied by independent commissioner and audit committee. The type of this research is quantitative research that uses secondary data based on annual report and financial report. A sample of this research consisted of 27 companies. Techniques analyzing data used panel data regression with random effects model and partial hypothesis testing (t test). Based on the results of data analysis, it can be concluded that independent commissioners and audit committees have no effect on tax avoidance. Meanwhile, management compensation has a significant positive effect on tax avoidance. From the result of the research show that the amount of compensation can influence management to carry out tax avoidance. Management will do tax avoidance if they get benefits, such as receiving management compensation. Keywords: Independent Commissioner, Audit Committee, Management Compensation, Tax Avoidance